Effects of DMSO on the Pluripotency of Cultured Mouse Embryonic Stem Cells (mESCs). (15th October 2020) - Sousa, Maria Inês; Correia, Bibiana; Branco, Ana Filipa; Rodrigues, Ana Sofia; Ramalho-Santos, João
Abstract : DMSO is a commonly used solvent in biological studies, as it is an amphipathic molecule soluble in both aqueous and organic media. For that reason, it is the vehicle of choice for several water-insoluble substances used in research. At the molecular and cellular level, DMSO is a hydrogen-bound disrupter, an intercellular electrical uncoupler, and a cryoprotectant, among other properties. Importantly, DMSO often has overlooked side effects. In stem cell research, the literature is scarce, but there are reports on the effect of DMSO in human embryoid body differentiation and on human pluripotent stem cell priming towards differentiation, via modulation of cell cycle. However, in mouse embryonic stem cell (mESC) culture, there is almost no available information. Taking into consideration the almost ubiquitous use of DMSO in experiments involving mESCs, we aimed to understand the effect of very low doses of DMSO (0.0001%-0.2%), usually used to introduce pharmacological inhibitors/modulators, in mESCs cultured in two different media (2i and FBS-based media). Our results show that in the E14Tg2a mESC line used in this study, even the smallest concentration of DMSO had minor effects on the total number of cells in serum-cultured mESCs. However, these effects could not be explained by alterations in cell cycle or apoptosis. Furthermore, DMSO did not affect pluripotency or differentiation potential. All things considered, and although control experiments should be carried out in each cell line that is used, it is reasonable to conclude that DMSO at the concentrations used here has a minimal effect on this particular mESC line.